THE REGIONAL PROVINCES OF PROTEROZIC RAPAKIVI GRANITE-ANORTHOSITE ASSOTIATION - MYTROKHYN, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The aria distribution, age and petrographic сomposition of rapakivi granite-anorthosite complexes are analysed at a modern level. Six regional petrographic provinces of the rapakivi granite-anorthosite association are marked out on the East Europe, North American and East Siberia cratons. The regular geological and petrographic description of most typical magmatic complexes of the association is resulted.